Unlawful Acts By The Notary/Ppat Against Land Rights Acquisition Duty (Bphtb) (Study Of Determination Of Bphtb Corruption Suspects In Batu City Government) - Prabowo, Adhitya Rizky; Aprillia.RS, Dwi Arassy (Universitas Malayati, 2024)
In practice, Notaries/PPATs often act as intermediaries for depositing BPHTB payments to facilitate the process of transferring land rights. The problem is that several Notary/PPAT individuals often abuse their authority in the realm of unlawful acts in carrying out their office in paying BPHTB Tax. This type of research is Normative Juridical. Based on the results of the discussion in this paper, the consequences of unlawful actions by a Notary in terms of reducing the land transaction price below the market value price by collaborating and providing compensation to other parties carries criminal and administrative sanctions. The conclusion from this discussion is that Notaries are responsible for helping clients pay BPHTB, not abusing their authority by lowering transaction prices and providing compensation to unscrupulous state administrators, thereby causing losses to the state. The legal consequences received by Notaries who abuse their authority are subject to criminal and administrative sanctions against their position. The unlawful nature of the criminal law alleged against the notary is stated expressively verbis in the formulation of the offense as having consequences as an element that must be and. Acts against the law can be used as a basis for criminal liability by fulfilling the formal and material elements that form the basis for criminal acts in BPHTB practice.